Between Crisis and Revival: Withdrawal Threats, State Exits, and Institutional Change of Regional International Organizations - Diana Panke; Lukas Grundsfeld; Pawel Tverskoi (Politische Vierteljahresschrift, 2024)
Since 1945, there have been more than 120 instances of states threatening to withdraw from international organizations with regional membership criteria (RIOs) and over 50 cases in which states in fact left RIOs. Recent examples include withdrawal threats by Qatar toward the Gulf Cooperation Council and Brazil toward MERCOSUR, as well as the actual exits of the United Kingdom from the European Union (EU) and of Burkina Faso, Mali, and Niger from the Economic Community of West African States. Withdrawal threats and exits represent shocks with potentially significant implications for RIOs and their integration projects. While existing research has focused on the future of EU integration after Brexit, this paper is the first to analyze the effects of threats to leave and the realization thereof on RIOs and regional integration from a broader comparative perspective. RIOs can respond to exit-related challenges through institutional change, which can take the form of institutional strengthening or weakening. Having conducted a series of explorative qualitative case studies, we find that while (1) the extent of problem pressure induced through exit-related challenges influences institutional change, (2) the materialization and directionality of these changes also depends on other factors, such as external windows of opportunity and the distribution of power and preferences within the RIO. Furthermore, (3) institutional change often takes the form of institutional strengthening, indicating the general resilience of international organizations in the context of exit-related challenges. – – Seit 1945 gab es mehr als 120 Fälle, in denen Staaten mit dem Austritt aus internationalen Organisationen mit regionalen Mitgliedschaftskriterien (RIOs) gedroht haben, und über 50 Fälle, in denen Staaten die RIOs tatsächlich verlassen haben. Zu den jüngsten Beispielen gehören die Austrittsdrohungen Katars gegenüber dem Golf-Kooperationsrat oder Brasiliens gegenüber dem MERCOSUR sowie die vollzogenen Austritte des Vereinigten Königreichs aus der Europäischen Union (EU) sowie von Burkina Faso, Mali und Niger aus der Wirtschaftsgemeinschaft Westafrikanischer Staaten (ECOWAS). Austrittsdrohungen und Austritte stellen Schocks mit potenziell erheblichen Auswirkungen auf RIOs und ihre Integrationsprojekte dar. Während sich die bisherige Forschung auf die Zukunft der EU-Integration nach dem Brexit konzentrierte, ist dieses Papier das erste, das die Auswirkungen eines drohenden Austritts und dessen Umsetzung auf RIOs und regionale Integration aus einer breiteren vergleichenden Perspektive analysiert. RIOs können auf die mit dem Austritt verbundenen Herausforderungen durch institutionelle Veränderungen reagieren, die die Form einer institutionellen Stärkung oder Schwächung annehmen können. Anhand einer Reihe explorativer qualitativer Fallstudien stellen wir fest, dass zwar (1) das Ausmaß des Problemdrucks, der durch die mit dem Ausstieg verbundenen Herausforderungen entsteht, den institutionellen Wandel beeinflusst, (2) das Zustandekommen und die Richtung dieser Veränderungen aber auch von anderen Faktoren abhängt, wie z. B. von externen Gelegenheiten und der Verteilung von Macht und Präferenzen innerhalb der RIO. Darüber hinaus (3) nimmt der institutionelle Wandel häufig die Form einer institutionellen Stärkung an, was auf die generelle Widerstandsfähigkeit von RIOs im Zusammenhang mit austrittsbezogenen Herausforderungen hindeutet.
Keywords: 320; Regional International Organizations (RIOs); Exit threats; Exits; Regional integration; Problem pressure; Regionalorganisation; Austrittsdrohung; Austritt; Regionale Integration; Problemdruck